PENGARUH PERKEMBANGAN SEKTOR PARIWISATA TERHADAP PENYERAPAN TENAGA KERJA DI PROVINSI JAWA TENGAH - Syaqina Arunda Salsabilla; Lorentino Togar Laut (Badan Perencanaan Pembangunan Daerah Kota Magelang, 2022)
The tourism sector plays an important role as a source of foreign exchange earnings, especially by reducing unemployment and increasing national productivity, which can encourage the country's economic growth. The purpose of this study is to find out how the tourism sector affects employment in Central Java Province in 2016-2020. The data used in this study is secondary data obtained from related sources which is then processed using panel data regression analysis with the Eviews 10 application. The results of this study indicate a positive and significant effect of the number of hotels on employment. While the variables of the number of tourist attractions and the number of restaurants have a negative and significant effect on employment in Central Java Province in 2016-2020.